ASPECTOS BIOLÓGICOS, COMPORTAMENTO DE CÓPULA E SENSILAS ANTENAIS DE BOTHYNUS STRIATELLUS (COLEOPTERA: SCARABAEIDAE: DYNASTINAE) - MARTINS, Gabriella Torres,; RODRIGUES, Sérgio Roberto, (ANAIS DO ENIC, 2023)
-